289 The EVE Study: Exercise, vascular health, and environment in Older Black and White females - McKenna Tharpe; Silvienne Sint Jago; Fitzgerald Dodds; Michael Hankes; Gareth Dutton; Raymond Jones; John Lowman; Adam Wende; Tom Buford (Journal of Clinical and Translational Science)
Objectives/Goals: Arterial stiffness is a determinant of vascular health. Older Black females exhibit greater arterial stiffness than White females. Exercise minimizes negative health effects of prolonged exposure to adverse social determinants of health (SDoH). Here, we will assess the role of exercise on race differences in arterial stiffness and SDoH in females. Methods/Study Population: We will recruit 96 postmenopausal females (48 Black, 48 White) from the Birmingham, AL area. Graded exercise tests will be used to define training status (“trained”: VO2max ≥60th percentile, “untrained”: ≤35th percentile). We will assess arterial stiffness via pulse wave velocity (SphygmoCor XCEL). SDoH will include income, education, neighborhood deprivation, racial discrimination, food insecurity, and healthcare access, all measured via corresponding surveys. We will then perform a two-way analysis of variance (race × training status) to assess the differences in arterial stiffness between groups. Through linear regression, we will evaluate the statistical relations between arterial stiffness and race, training status, and SDoH. Results/Anticipated Results: Our central hypothesis is that Black females will have greater arterial stiffness, by way of greater exposure to adverse SDoH, than White females, but that habitual aerobic exercise will attenuate this race difference. Ultimately, we aim to inform future clinical trials related to understanding female-specific cardiovascular disease progression. Discussion/Significance of Impact: Black females face significant exposure to adverse SDoH and have the highest rates of cardiovascular disease in the United States. However, females are still widely underrepresented in relevant research. This will be the first study to examine the roles of aerobic exercise, race, and SDoH in cardiovascular disease risk among females.